Itineraries of the Great War and the rise of the local on the Western Front: Memory, commemoration and the shifting regimes of remembrance tourism. (December 2020) - Ahmad, Rafiq; Hertzog, Anne
The mainstream grand narratives of the Great War have tended to disregard local perspectives from territories on the Western Front. Using on-the-field visits of battlefields, interviews with stakeholders and analysis of battlefield guidebooks and itineraries, this article addresses these gaps by examining local assertions in the re-invention of battlefield itineraries and remembrance trails of the Great War, the new socio-spatial order they establish and discordance of perspectives it triggers between the nation and the territory. The itinerary, thus, devised by memory entrepreneurs and performed by visitors on the ground becomes an 'effort of remembrance' and a dynamic scheme mediating between participants and place.